Polymorphism, Hydrogen Bond Properties, and Vibrational Structure of 1H-Pyrrolo[3, 2-h]Quinoline Dimers. (26th July 2012) - Gorski, Alexandr; Gawinkowski, Sylwester; Luboradzki, Roman; Tkacz, Marek; Thummel, Randolph P.; Waluk, Jacek
Abstract : Two forms of cyclic, doubly hydrogen-bonded dimers are discovered for crystalline 1H-pyrrolo[3, 2- h ]quinoline, a bifunctional molecule possessing both hydrogen bond donor and acceptor groups. One of the forms is planar, the other is twisted. Analysis of IR and Raman spectra, combined with DFT calculations, allows one to assign the observed vibrations and to single out vibrational transitions which can serve as markers of hydrogen bond formation and dimer structure. Raman spectra measured for samples submitted to high pressure indicate a transition from the planar towards the twisted structure. Formation of intermolecular hydrogen bonds leads to a large increase of the Raman intensity of the NH stretching band: it can be readily observed for the dimer, but is absent in the monomer spectrum.